# Chemical Forums

• January 16, 2019, 01:34:34 AM
• Welcome, Guest

•

Pages: [1]   Go Down

### AuthorTopic: How to derive ΔG∘=−RTlnKeq from ΔG∘= ΔH∘-T ΔS∘?  (Read 423 times) !function(d,s,id){var js,fjs=d.getElementsByTagName(s)[0];if(!d.getElementById(id)){js=d.createElement(s);js.id=id;js.src="https://platform.twitter.com/widgets.js";fjs.parentNode.insertBefore(js,fjs);}}(document,"script","twitter-wjs"); (function() {var po = document.createElement("script"); po.type = "text/javascript"; po.async = true;po.src = "https://apis.google.com/js/plusone.js";var s = document.getElementsByTagName("script")[0]; s.parentNode.insertBefore(po, s);})();

0 Members and 1 Guest are viewing this topic.

#### AussieKenDoll

• Regular Member
• Mole Snacks: +0/-0
• Offline
• Posts: 10
##### How to derive ΔG∘=−RTlnKeq from ΔG∘= ΔH∘-T ΔS∘?
« on: December 19, 2018, 05:26:33 PM »

How to derive ΔG∘=−RTlnKeq from ΔG∘= ΔH∘-T ΔS∘?
Logged

#### AussieKenDoll

• Regular Member
• Mole Snacks: +0/-0
• Offline
• Posts: 10
##### How to derive ΔG∘=−RTlnKeq from basic thermodynamic principles?
« Reply #1 on: December 19, 2018, 05:28:08 PM »

How to derive ΔG∘=−RTlnKeq from basic thermodynamic principles?
Logged

#### Borek

• Mr. pH
• Deity Member
• Mole Snacks: +1619/-395
• Online
• Gender:
• Posts: 24732
• I am known to be occasionally wrong.
##### Re: How to derive ΔG∘=−RTlnKeq from ΔG∘= ΔH∘-T ΔS∘?
« Reply #2 on: December 19, 2018, 09:07:34 PM »